Factors mediating plastid dependency and the origins of parasitism in apicomplexans and their close relatives - Janouškovec, Jan (Proc Natl Acad Sci U S A, 2015)
Apicomplexans are a major lineage of parasites, including causative agents of malaria and toxoplasmosis. How such highly adapted parasites evolved from free-living ancestors is poorly understood, particularly because they contain nonphotosynthetic plastids with which they have a complex metabolic dependency. Here, we examine the origin of apicomplexan parasitism by resolving the evolutionary distribution of several key characteristics in their closest free-living relatives, photosynthetic chromerids and predatory colpodellids. Using environmental sequence data, we describe the diversity of these apicomplexan-related lineages and select five species that represent this diversity for transcriptome sequencing. Phylogenomic analysis recovered a monophyletic lineage of chromerids and colpodellids as the sister group to apicomplexans, and a complex distribution of retention versus loss for photosynthesis, plastid genomes, and plastid organelles. Reconstructing the evolution of all plastid and cytosolic metabolic pathways related to apicomplexan plastid function revealed an ancient dependency on plastid isoprenoid biosynthesis, predating the divergence of apicomplexan and dinoflagellates. Similarly, plastid genome retention is strongly linked to the retention of two genes in the plastid genome, sufB and clpC, altogether suggesting a relatively simple model for plastid retention and loss. Lastly, we examine the broader distribution of a suite of molecular characteristics previously linked to the origins of apicomplexan parasitism and find that virtually all are present in their free-living relatives. The emergence of parasitism may not be driven by acquisition of novel components, but rather by loss and modification of the existing, conserved traits.